The Characteristics of Preeclampsia and Eclampsia Patients at Dr. T.C. Hillers Regional Hospital Maumere - Sentosa, I Gede Bagus; Kurniawan, Rommy Andika; Conterius, Advent CT (Fakultas Kedokteran Universitas Brawijaya, 2024)
Preeclampsia can occur from the time the mother is pregnant until 48 hours to 6 weeks after giving birth and is associated with an increased complication rate of 2-8% during pregnancy, contributing to 9 - 26% of maternal deaths. This condition can have significant prolonged effects on both the mother and the baby. Considering the high rates of morbidity and mortality in mothers and babies due to preeclampsia, this study aims to understand the characteristics of patients with preeclampsia at T.C. Hillers Regional Hospital of Maumere within the period of January 1st to December 31st, 2022. This study is a retrospective descriptive study using secondary data. The data collection was performed on patients diagnosed with preeclampsia and eclampsia during the study period. The results showed that most participants were between 20-34 years old, had a body mass index (BMI) of ≥ 25, multigravida (had multiple pregnancies), housewives, High School graduates, and had a history of chronic hypertension. Based on risk factors, 35.5% of the subjects were ≥ 35 years old, 31% were primigravida (first-time pregnant), 26% were obese, 21% had a history of hypertension in previous pregnancies, 10,5% had chronic hypertension, 3% had multiple gestations, 1% of the subjects had a pregnancy interval >10 years, and 0.5% had diabetes mellitus. This study provides an overview of the characteristics and risk factors of pregnant women with preeclampsia in Maumere.